Crime and punishment in Norwegian mid-adolescents: a normal population study - Pedersen, Willy (Journal of Scandinavian studies in criminology and crime prevention, 2000)
Does the 'penal eye' of our society most easily catch sight of those with scant resources and lower-class backgrounds? In a national representative sample of Norwegian adolescents, we investigated the selection process to the penal system. Of the adolescents studied, 2.8% had received a penal sanction during the last year, 3.7% of the boys and 1.9% of the girls. The sanctions varied in seriousness, from a ticket fine to a prison sentence. These adolescents had much higher crime participation than other adolescents. In particular, substance-related offences were of importance. They had a high frequency of alcohol intoxication, and they often had a previous history of police contacts. No links were found to parental social class, but there was an association with parental history of unemployment. Furthermore, numerous other parental risk factors were found, such as marital breakup, low level of care, lack of monitoring and frequent alcohol intoxication. However, these factors were also associated with the development of crime. Were such extra-legal factors predictors of penal sanctions, when crime, alcohol intoxication and a previous history of police contacts were controlled for? Poor parental monitoring was the only (marginally) significant predictor. On the other hand, criminal behaviour had a highly significant effect, as early as at the lowest level of participation, and this effect increased steeply at higher levels. Alcohol had an effect, but only when the adolescents reported a rather high number of intoxication episodes. Thus, a problematic family background and small resources obviously play a role in the development of crime, but are less important as direct factors of being caught by the police and punished by the penal system. However, the subjects in our sample were still in their midteens and it might well be that development in late adolescence and young adulthood takes a different course